Contrasting photoreactivity of β2-adrenoceptor agonists Salbutamol and Terbutaline in the presence of humic substances. (August 2019) - Zhou, Lei; Sleiman, Mohamad; Fine, Ludovic; Ferronato, Corinne; de Sainte Claire, Pascal; Vulliet, Emmanuelle; Chovelon, Jean-Marc; Xiu, Guangli; Richard, Claire
Abstract: The photodegradation reactions of two typical β2-adrenoceptor agonists, salbutamol (SAL) and terbutaline (TBL), alone, and in the presence of Aldrich humic acid (AHA) or Suwannee River fulvic acid (SRFA) were investigated by steady-state photolysis experiments, laser flash photolysis (LFP), kinetic modeling and quantum calculation. AHA and SRFA (2–20 mgC L −1 ) accelerated the phototransformation of both SAL and TBL. For SAL, an inhibiting effect of oxygen on the photodegradation was observed that is fully consistent with the main involvement of excited triplet states of HS ( 3 HS*). On the contrary, oxygen drastically enhanced the photodegradation of TBL showing that 3 HS* were negligibly involved in the reaction. The involvement of singlet oxygen was also ruled out because of the low reaction rate constant measured between TBL and singlet oxygen. Quantum calculations were therefore performed to explore whether oxygenated radicals could through addition reactions explain the differences of reactivity of TBL and SAL in oxygen medium. Interestingly, calculations showed that in the presence of oxygen, the addition of phenoxyl on TBL led to the formation of adducts and to the loss of TBL while the same addition reaction on SAL partly regenerated the starting compound and at the end degraded SAL less efficiently. This study is of high relevance to understand the processes involved in SAL and TBL phototransformation and the photoreactivity of HS. Moreover, our findings suggest that TBL might be a promising probe molecule to delineate the role of oxygenated radicals. Graphical abstract: Image 1 Highlights: HS-mediated photodegradations of Salbutamol and Terbutaline were compared. Oxygen affected the reactions very differently. 3 HS* is responsible for Salbutamol photodegradation but not for that of terbutaline. Quantum calculations were performed to test the effect of phenoxyl radicals. Oxygenated radicals might be involved in the terbutaline phototransformation.